حماية الشهود من خلال أسباب الإباحة في الفقه الإسلامي - طهراوي, زوبير (University of Eloued جامعة الوادي, 2022)
ألزمت الشّريعة الشّهود بأداءِ الشهادة ونهت عن كتمانها لما في ذلك من تضييعٍ للحقوق وإخفاءٍ للحقائق، ووفّرت لهم حماية خاصة من خلال إباحة بعض الأفعال المجرّمة كالسّبّ أو القذف، أو إفشاء أسرارٍ مُؤْتَمَنين عليها، بصفتهم شهودًا يُدلُون بشهادتهم أمام القاضي. وسنتناول في هذه الدراسة الحماية التي خصّها الفقه الاسلامي للشهود من خلال أسباب الإباحة، بالتّطرق إلى مفهوم أسباب الإباحة في الفقه الاسلامي ثم حماية الشهود من جرائم السب والقذف وإفشاء السر المهني. : Abstract The Islamic Sharia obliges witnesses to give their testimonies and forbids to hide them due to the loss of rights and concealing facts. It provides them a special protection through permitting some forbidden deeds such as insulting, slandering and disclosuring of trusty secrets in capacity of witnesses before the judge. In this study, we will deal with the protection provided by the Islamic jurisprudence to the witnesses .through the reasons of permissibility from the crimes of insulting, slandering and disclosuring of professional secrets
Keywords: الكلمات المفتاحية: الشهود؛ أسباب الإباحة؛ السب؛ القذف؛ السر المهني؛ ; key words: Witnesses; Reasons for permissibility; Insulting, Slandering Professional secrets.